2012
DOI: 10.1108/13673271211246167
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge sharing motivational factors of using an intra‐organizational social media platform

Abstract: PurposeThis paper aims to discuss the motivational factors affecting the knowledge sharing through an intra‐organizational social media platform and to answer the following research questions: “What motivates employees to share their knowledge through an intra‐organizational social media platform?”; “What impedes them sharing knowledge this way?”; and “Do these factors differ from those motivational factors regarding knowledge sharing in general?”.Design/methodology/approachThe paper approaches the issue from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
106
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 182 publications
(139 citation statements)
references
References 41 publications
9
106
1
5
Order By: Relevance
“…This perceived cost refers to a knowledge sharing barrier, in which participants mentally assess contribution efforts: if the mental effort and time outweigh the overall benefit, they refuse to participate in an ENoP system. This finding is consistent with Vuori and Okkonen's (2012) study in which they found effort to be an important individual cost of participation in intra-organizational social media.…”
Section: Perceived Costssupporting
confidence: 83%
See 4 more Smart Citations
“…This perceived cost refers to a knowledge sharing barrier, in which participants mentally assess contribution efforts: if the mental effort and time outweigh the overall benefit, they refuse to participate in an ENoP system. This finding is consistent with Vuori and Okkonen's (2012) study in which they found effort to be an important individual cost of participation in intra-organizational social media.…”
Section: Perceived Costssupporting
confidence: 83%
“…Although the ENoP's platform is a simple platform and networks' experts have skills to use technical features, time is a significant cost of participation. This finding is consistent with Vuori and Okkonen (2012) study, who found that users of organizational social media indicate that time is a significant barrier to sharing knowledge. Further, the effort for knowledge contributing through ENoPs is identified as an individual perceived cost of knowledge sharing-individual mental and physical efforts to acquire, create, document and share knowledge through ENoPs (Sun et al 2014).…”
Section: Perceived Costssupporting
confidence: 83%
See 3 more Smart Citations